Swarm, evolutionary, and memetic computing : 5th International Conference, SEMCCO 2014, Bhubaneswar, India, December 18-20, 2014 : revised selected papers /: 5th International Conference, SEMCCO 2014, Bhubaneswar, India, December 18-20, 2014 : revised selected papers. ([2015]) - Unknown
No abstract available